An effective approach to obtain high efficiency red light-emitting polymers via incorporating benzodithiazole units. (September 2018) - Liu, Zhitian; Fang, Cheng; Cai, Xiang; Gao, Xiang; Li, Pengcheng; Zhang, Qi; Tu, Guoli
Abstract: Two conjugated polymers using 5, 6-dialkoxy benzothiadiazole derivatives as the dopant were synthesized and studied as electroluminescent materials. These two polymers were well characterized by 1 H NMR, UV–Vis absorption spectrum, gel permeation chromatography, fluorescent spectrum and cyclic voltammetry. The electron mobility and electroluminescent properties were also investigated. The highest external quantum efficiency and luminous efficiency were improved by two orders of magnitude facilely via incorporating benzothiadiazole unit in the main chain. Graphical abstract: Highlights: Incorporating benzothiadiazole units in the main chain boosted the EL performance. 5, 6-bis(alkoxy)benzothiadiazole-based red-emitting EL materials were studied. Efficient and stable red-emitting PLEDs were fabricated.